Sistem Waris Penduduk Pribumi Mandala Desa Campursari Kecamatan Megang Sakti Kabupaten Musi Rawas Perfektif Hukum Islam di Indonesia - Laras Shesa; Busra Febriyarni (Institut Agama Islam Negeri (IAIN) Curup, 2021)
The purpose of the study was to figure out how the inheritance system differences of the indigenous mandala population with islamic law. Indigenous residents are natives who settled in Mandala designation of the Megang Sakti Campusari Village area of Musi Rawas County South Sumatra Province. This research is field research or field research. In reviewing primary data obtained from author interviews using a qualitative approach. From the research done then the authors get the results of the study that the inheritance system of the Indigenous Mandala population is incompatible with the syarat’ and the Compilation of Islamic Law (KHI). It is due to Islamic law and KHI article 174. Kinship due to the nasab is not only the descendant of the lower heir, but rather there are from the ancestors of the upward heir like father or grandfather and sideways like siblings and a father of heir. The part of the boy's inheritance when heirs with daughters is twice the part of girls, meaning the part of girls half of the part of boys. It is set in articles 176 to 182 KHI. In article 209 KHI the adopted child section is restricted to a maximum of one-third of the inheritance property through mandatory wills